Strengthening the Capacity of Education Staff to Support the Wellbeing of Indigenous Students in Boarding Schools: A Participatory Action Research Study - Marion Heyeres; Janya McCalman; Erika Langham; Roxanne Bainbridge; Michelle Redman-MacLaren; Amelia Britton; Katrina Rutherford; Komla Tsey (The Australian Journal of Indigenous Education, 2019)
In meeting the social and emotional learning (SEL) needs of Aboriginal and Torres Strait Islander students, the capacities of school staff are critical. There is very limited evidence for relevant capacity development initiatives. This evaluation reports a multicomponent SEL training intervention delivered to staff of an Australian education service that operates independently of any particular school to assist with the transitions of students from remote communities to boarding schools. A participatory action research (PAR) approach was implemented over 13-months with 21 staff participants. Results from a pre-, mid- and six months post-training survey and staff interviews were analysed and fed back through reflective group discussions. The training was associated with improved staff attitudes to mental health and skills to support student wellbeing. Sixteen participants received a tertiary qualification. Despite ‘working in challenging environments’, staff were ‘dedicated to help’ students, and ‘acknowledged the need for change’ to better support student wellbeing. However, given the service's brokering role between families and schools, fewer staff members reported feeling empowered to influence issues in their workplace. The evaluation demonstrated the value of SEL training for education staff and potential utility for school teachers and boarding staff who have direct duty of care for Indigenous students. The multicomponent training described in this study would need to be condensed for school settings.